ANALISIS EFISIENSI PEMASARAN JAGUNG (ZEA MASYS L) DI DESA DONE KECAMATAN MAGEPANDA KABUPETAN SIKKA - Karmila, Karolina; Anggriani, Yohana; Otan Apelabi, Gabriel (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine marketing channels, marketing margins and marketing efficiency of corn in Done Village, Magepada District, Sikka Regency. This type of research is quantitative descriptive analysis research. The sampling technique for farmer respondensts used 15% random sampling with a total of 180 corn farmers with a total sample taken of 36 corn farmers, while traders were taken based on the census, numbering 4 people consisting of 2 collectors and 2 retailers and 2 Consumers were only taken as samples, 1 costumer bought directly form farmers and 1 costumers bougth from retails. The results of this research are that there are 3 marketing channels for corn in Done Village, Magepada District, Sikka Regency, consisting of 1 direct marketing channels and 2 indirect marketing chaanels. The marketing margin of corn in Done Village, Magepada District, Sikka Regency is marketing channels I without marketing margin, marketing channels II IDR 3.500 and marketing channels III IDR 4.500 and corn marketing effciency in Done Village, Magepada District, Sikka Regency is marketing channels I 7,14%, marketing channels II 15,38% and marketing channels III 27,27%.